Analisis Pengaruh Budaya Organisasi, Karakteristik Kerja, dan Stres Kerja, Terhadap Kepuasan Kerja dan Kinerja Karyawan PT. PLN (Persero) Rayon Kalabahi Kabupaten Alor - Mesak Y. Awang; Alvonso F. Gorang; Yeny M. Allung (Universitas Sam Ratulangi, 2022)
The purpose of this research is to get an overview of organizational culture, work characteristics, job stress, and its impact on employee performance as a cause of job satisfaction. the subject of this survey is PT. PLN (Persero) area of Kalabahi. The number of samples in the study amounted to 55 people who can be processed in the analysis. Data analysis method using Smart Partial Least Square (SmartPLS). The survey results show that organizational culture has a direct and significant effect on job satisfaction and employee performance. Job characteristics have no effect on job satisfaction. Although it has a positive impact, job characteristics do not directly affect employee performance. Job stress has a significant effect on job satisfaction but has a negative impact on employee performance. Furthermore, work characteristics are not factors that affect employee performance, but are factors that affect job satisfaction, so it is very important to create a corporate culture and minimize employee work stress so that we can increase job satisfaction and encourage employee performance growth.